The Influence Of Store Atmosphere, Brand Image And Service Quality On Coffee Purchasing Decisions (Case Study At Konnichiwa Shop, Bengkulu City) - Agung Sutiyo Wibowo; Khairul Bahrun (Penerbit Jurnal Indonesia, 2024)
The aim of the research is to determine the influence of Store Atmosphere, Brand Image and service quality on coffee purchasing decisions (case study at Konnichiwa Shop, Bengkulu City) and to find out which factors most dominantly influence purchasing decisions. This research used quantitative methods on 190 respondents. The population used in this research is consumers of Kedai Konnichiwa, Bengkulu City and sampling in this research uses a non-probability sampling technique. Based on the results of multiple linear regression, the regression equation Y = 16.916 + 0.292 (X1), + 0.456 (X2) + 0.332 (X3) is obtained. The results of the research concluded that Store Atmosphere, Brand Image and Service Quality had a positive and significant effect, both partially and simultaneously, on Purchase Decisions at Konnichiwa Stores in Bengkulu City.